Pengaruh Literasi Tentang Riba, Faktor Sosial Dan Faktor Pribadi Terhadap Keputusan Nasabah Memilih Jasa Perbankan Syariah Pada Bank Syariah Indonesia KCP SUNGAI LILIN - Eryani, Risma; Umari, Zuul Fitriani; Juniawati, Mutmainah (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This reseach article uses a quantitative approach to analyze how literacy about usury, social factors and personal factors affect customer decisions in choosing sharia banking services at BSI KCP Sungai Lilin. Data obtained by distributing questionnaires to BSI KCP Sungai Lilin customers with a total sample of 275 customers through accidental sampling techniques. Data analysis of this reseach article used multiple linear analysis with the help of IMB SPSS 26 data processing software. The results of data analysis of reseach articles show that literacy about usury doesn’t affect customers decisions in using sharia Banking services. While social factors and personal factors affect customer decisions in using sharia banking services. Simultaneously literacy about usury, social factors and personal factors influence customer decicions to use sharia banking services at BSI KCP Sungai Lilin.